Valsartan to Prevent Acquired Pulmonary Vein Stenosis in Pediatric Patients After Total Anomalous Pulmonary Venous Connection Surgery - Jin Shentu; Mingjie Zhang; Zhuoming Xu; Chen Wen; Hao Zhang; Zhongqun Zhu; Huiwen Chen; Guocheng Shi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Recurrent pulmonary vein stenosis (PVS) following surgical repair of total anomalous pulmonary venous connection is associated with poor prognosis. Preclinical studies have shown that use of an angiotensin receptor blocker can attenuate intimal hyperplasia; notwithstanding, its clinical utility is of uncertain benefit. Methods This single‐center study included patients undergoing total anomalous pulmonary venous connection repair in 2020 to 2021. Since August 2020, patients have been considered for valsartan therapy early after operation. Contemporaneous participants were subcategorized into study versus control groups based on valsartan exposure. Patients in the control group were treated with the same protocolized algorithm except valsartan administration. The primary end point was postoperative PVS (PPVS) progression. Results Overall, 104 patients operated on at a median age of 1.3 months were included (valsartan group: 25 versus control group: 79). The baseline characteristics were similar between the 2 groups. Within a median follow‐up of 28.6 months, 27 patients developed PPVS noted by echocardiography and computed tomography angiography, among which 22 with clinical PPVS underwent reoperations. No between‐group difference was observed in the incidence of initial PPVS (P=0.80, Cohen's h=0.06 [95% CI, −0.38 to 0.50]) and reoperation (P=0.46, Cohen's h=−0.18[ 95% CI, −0.65 to 0.29]); however, patients in the valsartan group had a significantly lower risk of PPVS progression (P=0.019, Cohen's h=−1.12 [95% CI, −1.66 to −0.57]) and subsequent PPVS progression after reoperation (P=0.011, Cohen's h=−1.71 [95% CI, −2.61 to −0.82]) compared with the control group. PPVS‐related death was observed in 9 cases (11.4%) in the control group versus none (0%) in the valsartan group. No adverse event related to valsartan occurred in this series. Conclusions Early use of valsartan after total anomalous pulmonary venous connection surgery appears to potentially be a feasible and effective adjunct to reoperation in treating pediatric acquired PVS.